Cultural roots of healing: exploring traditional medicine practices of the Nocte tribe of Arunachal Pradesh - Miatcha Tangjang; Ajay Maletha
Traditional medicine plays a vital role in the survival of Indigenous tribal communities in remote rural regions of Arunachal Pradesh, where access to modern healthcare system is often limited. This study documents the traditional medicinal knowledge related to flora and fauna utilized by the Nocte tribe of Arunachal Pradesh over two years (2022-2024) through semi-structured questionnaires. The study identified the use of 34 plant species across 22 families, primarily targeting gastrointestinal issues (45%), blood coagulation (19%), and high blood pressure (9%). Informant Consensus Factor (ICF) analysis showed a high degree of knowledge homogeneity (ICF=1.00) for plants used to treat typhoid, colds and coughs, dental issues, and general illnesses. High use value (UV=2.00) was recorded for species including Artemisia sp., Solanum aethiopicum, Solanum indicum, Centella asiatica, Zanthoxylum armatum, Curcuma longa, Goniothalamus sp., and Terminalia chebula. The highest family use values (FUV=2.00) were observed in the Apiaceae, Annonaceae, and Combretaceae families. Several species, including Ageratum conyzoides, Artemisia sp., Chromolaena odorata, Mikania scandens, Oxalis corniculata, Solanum spp., Centella asiatica, Citrus medica, Zanthoxylum sp., Clerodendrum venosum, Curcuma longa, Zingiber officinale, Emblica officinalis, Goniothalamus sp., Hydrocotyle sibthorpioides, Musa paradisiaca, and Potentilla indica, exhibited a Relative Frequency of Citation (RFC=1.00), indicating high recognition among informants. Additionally, the study found that 11 animal species, predominantly mammals (64%), were also utilized medicinally. Hystrix brachyura, Apis mellifera, and Apis cerana had the highest RFC (0.034), indicating less use frequency compared to plants. This study highlights the importance of documenting and preserving this eroding traditional knowledge, to revitalize its relevance among younger generations and protect the cultural heritage of these communities.